2005
DOI: 10.1097/00042737-200511000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A candidate gene approach of immune mediators effecting the susceptibility to and severity of upper gastrointestinal tract diseases in relation to Helicobacter pylori and Epstein???Barr virus infections

Abstract: This review focuses on immunogenetic aspects of diseases of the upper gastrointestinal tract in which infectious agents may play a role in the aetiopathogenesis, such as Helicobacter pylori, Epstein-Barr virus (EBV) and HIV. Gastric adenocarcinoma is a common cancer all around the world, with declining incidences in Europe and high incidences in Asia and central and south America. Together with gastric atrophy and peptic ulcer disease, gastric adenocarcinoma belongs to the commonest upper gastrointestinal trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…In this study, we measured seropositivity of H. pylori antibody and found that the interactions between seropositivity for H. pylori and EBV VCA IgG and EBNA IgG were not statistically significant (P ¼ 0.87 and P ¼ 0.79, respectively; data not shown). However, an interaction between both infections might be plausible, as both H. pylori and EBV infection have a role in carcinogenesis in the pathway of inflammation, chronic infection, and autoimmune pathway (Ouburg et al, 2005;Gwack et al, 2006). Several candidate gene approach studies suggest that EBNA genes interact with inflammatory and tumour suppressor genes, which has implications in gastric carcinogenesis (Ouburg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we measured seropositivity of H. pylori antibody and found that the interactions between seropositivity for H. pylori and EBV VCA IgG and EBNA IgG were not statistically significant (P ¼ 0.87 and P ¼ 0.79, respectively; data not shown). However, an interaction between both infections might be plausible, as both H. pylori and EBV infection have a role in carcinogenesis in the pathway of inflammation, chronic infection, and autoimmune pathway (Ouburg et al, 2005;Gwack et al, 2006). Several candidate gene approach studies suggest that EBNA genes interact with inflammatory and tumour suppressor genes, which has implications in gastric carcinogenesis (Ouburg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, an interaction between both infections might be plausible, as both H. pylori and EBV infection have a role in carcinogenesis in the pathway of inflammation, chronic infection, and autoimmune pathway (Ouburg et al, 2005;Gwack et al, 2006). Several candidate gene approach studies suggest that EBNA genes interact with inflammatory and tumour suppressor genes, which has implications in gastric carcinogenesis (Ouburg et al, 2005). In the analysis of EBNA, EA, and VCA antibodies, immunofluorescence assay methods are more time consuming and difficult to interpret, but are more specific, have high resolution, and stand as the 'gold standard' technique.…”
Section: Discussionmentioning
confidence: 99%
“…Because the ancestral parents are fully sequenced, the genotyped RI strains afford a powerful tool for identifying genes within QTLs and are particularly useful for mapping multiple and epistatic genetic effects underlying complex phenotypes, including those seen in infectious diseases. 22,47,[50][51][52] Among the different RI sets of mice, we found the BXD panel more suitable for us than other series (for example, the AXB set) as the BXD series is much larger, almost three-times more than used in any other series of experiments and because both parental strains (C57BL/ 6J and DBA/2J) have been fully sequenced, 30 and have been shown to differ in their response to many pathogens, 28,[53][54][55][56][57] …”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes are in general a double-edged sword, they promote carcinogenesis, as has been shown for multiple cancer sites, but a sufficient expression of inflammatory cytokines is also of utmost importance for a functioning innate immune system. Several reports suggest a relevance of variants in IL1 genes in susceptibility to and clearance of infectious agents [66,67] as well as the progression of related diseases [68,69]. Viruses, namely EBV, HTLV-I, and HCV, and bacteria, such as Helicobacter pylori, play a significant role in an increasing number of lymphoma subtypes [5,70].…”
Section: Discussionmentioning
confidence: 99%